The COVID-19 pandemic, stress, and trauma in the disability community: A call to action - Lund, Emily M; Forber-Pratt, Anjali J; Wilson, Catherine; Mona, Linda R (Rehabilitation psychology, 2020)
To inform the field of rehabilitation psychology about the impacts of the 2019 novel coronavirus (COVID-19) on the disability community in the United States and the additional sources of stress and trauma disabled people face during these times. A review of the literature on disability and COVID-19 is provided, with an emphasis on sources of trauma and stress that disproportionately impact the disability community and the ways in which disability intersects with other marginalized identities in the context of trauma and the pandemic. We also reflect on the potential impacts on the field of psychology and the ways in which psychologists, led by rehabilitation psychologists, can support disabled clients and the broader disability community at both the individual client and systemic levels. The COVID-19 pandemic introduces unique potential sources of trauma and stress within the disability community, including concerns about health care rationing and ableism in health care, isolation, and the deaths and illnesses of loved ones and community members. Rehabilitation psychologists and other professionals should be aware of the potential for trauma and stress among disabled clients and work with them to mitigate its effects. Additionally, psychologists should also work with the disability community and disabled colleagues to address systemic and institutional ableism and its intersections with other forms of oppression. (PsycInfo Database Record (c) 2021 APA, all rights reserved).